Natural resources rents and economic performance: Post-COVID-19 era for G7 countries. (March 2022) - Hordofa, Tolassa Temesgen; Liying, Song; Mughal, Nafeesa; Arif, Asma; Minh Vu, Hieu; Kaur, Prabjot
Abstract: COVID-19 affected the economies of both developed and developing countries through multiple channels. However, the impact of this pandemic was also not so different for the developed world too. This study aims to evaluate the effect of the natural resources' rents such as oil, natural gas and energy rents on the economic performance of G7 economies from 1990 to 2020. This study uses updated panel data methods to identify the effect of COVID-19 by using novel diagnostic and unit root methods. The study found that during the COVID-19 and post pandemic, economic performance has been declined. This study found that natural resources rent, including oil and gas, help to improve the economic performance. Further, structural break for the year 2019 caused by COVID-19 also slowed down the economic performance of G7 economies. This study suggests more stabilization policies towards natural resources commodity prices and encouragement of active role from the G7 countries. This study further provides relevant policy implications in the concluding section for the selected group of countries. Highlights: Commodity price volatility and economic growth in the Covid-19 era has been tested. AMG and CCEMG has been employed on the panel of G7 economies. Oil and natural gas rents increase economic performance. Total natural resource rents and energy related inflation reduces economic growth. Bidirectional causality has been confirmed among the variables.